EFFECT OF GARLIC (ALLIUM SATIVUM) AND GINGER (ZINGIBER OFFICINALE) AS FEED ADDITIVES ON BLOOD PROFILE AND BROILER PERFORMANCE - Karangiya, VA; Sasvani, HH; Padodara, RJ; Ribadiya, NK; Ribadiya, SJ (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was undertaken to investigate the effect of incorporating garlic and ginger powder, as a growth promoter in broiler feed . 240 day-old commercial broiler chicks (Cobb-400) were divided equally into four groups of 60 birds each, and were assigned to four isocaloric isonutritive diets, viz., Diet-I basal control diet without additives, Diet-II, basal diet + 1 % garlic, Diet-III, basal diet + 1 % ginger and Diet-IV, basal diet + mixture of 1 % garlic and 1 % ginger. The experiment was conducted in three replicates each of 20 birds. Feed and water were offered ad libitum . The starter and finisher diets were given to birds from 1 to 28 and 29 to 42 days of age, respectively. Growth performance parameters and blood parameters were measured. Broilers fed Diet - IV had significantly (P<0.05) increased feed intake. Body weight, body weight gain and efficiency of feed utilization of birds were superior with Diet-III. Dressing percentage showed no significant difference between the various dietary treatments. All three different dietary treatments significantly (P<0.05) suppressed haemoglobin and packed cell volume, and increased total erythrocytes and total leucocytes counts as compared to control diet, but the values of all were within normal range. It was thus concluded that the incorporation of garlic and ginger as feed additives at 1 % level significantly enhanced growth performance of broiler chicks without side effects as detected by normal blood profile.